Challenges from the disastrous COVID-19 pandemic: exposure to opportunities for branchless banking in Malaysia - Khairi Azhar Aziz; Marzanah A. Jabar; Salfarina Abdullah; Rozi Nor Haizan Nor (Institute of Advanced Engineering and Science, 2022)
Branchless banking is a new digitalization of artificial intelligence (AI) for future banking services. The rapid digitalization and technological advancement of financial institutions (FI) have changed due to the COVID-19 pandemic. Such branchless banks are expected to offer financial customers meaningful access whilst promoting responsible usage of suitable and affordable financial solutions. The objectives of this paper are to identify CSF to conduct branchless banking for bank performance during the attack of the COVID-19 pandemic in Malaysia. These CSFs are important to reinforce the new business model recommended by the central bank of Malaysia (BNM). Through this study five CSFs have been identified which are customers do not physically attend to the bank for their banking needs, it is more efficient, saves time, secured, and low cost. As the industrial revolution (IR) 4.0 approaches, public acceptance, innovation, and strong financial services, as well as demand of digital payment will take over the country. National savings bank (BSN) was officially the first bank in Malaysia to conduct branchless banking through agent banking. In line with the BNM division strategy 2011–2020, BSN had launched banking beyond branches via BSN agents who offer banking services on behalf of BSN.